Genetic susceptibility to type 1 diabetes in childhood - estimation of HLA class II associated disease risk and class II effect in various phases of islet autoimmunity - Ilonen, J; Kiviniemi, M; Lempainen, J; Simell, O; Toppari, J; Veijola, R; Knip, M (Pediatric diabetes, 2016)
Objective The HLA‐DR/DQ region remains the major determinant of susceptibility to type 1 diabetes (T1D) despite the more than 50 risk affecting loci outside human leukocyte antigen (HLA) region that have been identified. We aimed at developing a simple risk estimation based on HLA class II genotyping, which was also tested by analyzing HLA class II effect on the autoantibody seroconversion and further progression to diabetes. Subjects and methods A total of 2991 trio families with a diabetic child from the Finnish Pediatric Diabetes Register were genotyped and the risk contributed by each DR‐DQ haplotype calculated through transmission analysis. The genotype risk was estimated based on the summary effect of haplotypes. Genotype grouping was further tested in a subcohort of the Finnish Type 1 Diabetes Prediction and Prevention (DIPP) Study Results The summary effect of haplotypes was generally seen in genotypes, while the expected synergistic effect of DR3‐DQ2 and DR4‐DQ8 (DRB1*04:03 excluded) combination was also clear in the T1D risk association analysis. This highest risk DR/DQ genotype was found in 21.6% of patients and 2.0% of controls, odds ratio (OR) = 13.2 (10.1–17.2), whereas the lowest risk genotype contained only 0.8% of patients and 28.0% of controls, OR = 0.02 (0.01–0.03). In the subcohort from the DIPP study the risk grades correlated clearly with seroconversion for islet autoantibodies and T1D development. In contrast, DR/DQ risk groups did not associate with the progression rate from advanced autoimmunity to clinical diabetes. Conclusions Class II HLA genotype groups improve the estimation of T1D risk. Class II effect is limited to the early phase of the disease process characterized by seroconversion for islet autoantibodies.